A de novo deletion in a boy with cerebral palsy suggests a refined critical region for the 4q21.22 microdeletion syndrome. Issue 5 (3rd April 2017) - Zarrei, Mehdi; Merico, Daniele; Kellam, Barbara; Engchuan, Worrawat; Scriver, Tara; Jokhan, Rikash; Wilson, Michael D.; Parr, Jeremy; Lemire, Edmond G.; Stavropoulos, Dimitri J.; Scherer, Stephen W.
Abstract : We present an 18‐year‐old boy with cerebral palsy, intellectual disability, speech delay, and seizures. He carries a likely pathogenic 1.3 Mb de novo heterozygous deletion in the 4q21.22 microdeletion syndrome region. He also carries a 436 kb maternally‐inherited duplication impacting the first three exons of CHRNA7 . The majority of previously published cases with 4q21.22 syndrome shared common features including growth restriction, muscular hypotonia, and absent or severely delayed speech. Using copy number variation (CNV) data available for other subjects, we defined a minimal critical region of 170.8 kb within the syndromic region, encompassing HNRNPD . We also identified a larger 2 Mb critical region encompassing ten protein‐coding genes, of which six ( PRKG2, RASGEF1B, HNRNPDL, HNRNPD, LIN54, COPS4 ) have a significantly low number of truncating loss‐of‐function mutations. Long‐range chromatin interaction data suggest that this deletion may alter chromatin interactions at the 4q21.22 microdeletion region. We suggest that the deletion or misregulation of these genes is likely to contribute to the neurodevelopmental and neuromuscular abnormalities in 4q21.22 syndrome.